2015
DOI: 10.1177/0023830914565688
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tonal Onglides in German Nuclear Pitch Accents

Abstract: A perception experiment with native German listeners provided evidence for the relevance of the tonal onglide in nuclear accents--the pitch movement leading towards the target on the accented syllable. Listeners were able to distinguish between two pragmatic meanings of a short phrase (given/non-contrastive and new/contrastive) using the tonal onglide as the sole acoustic cue. On the basis of these findings, we argue that the onglide merits a phonological status in an intonation model of German and should not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Figure 1B provides a schematic depiction of the tonal onglide measure. Tonal onglide characterizes the portion of the f0 movement toward the main tonal target of the pitch accent (Ritter and Grice, 2015;Roessig et al, 2019). In terms of an autosegmental-metrical analysis, like GToBI (Grice et al, 2005), L+H * , and H * pitch accent types are described by a rising movement and result in positive onglide values.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1B provides a schematic depiction of the tonal onglide measure. Tonal onglide characterizes the portion of the f0 movement toward the main tonal target of the pitch accent (Ritter and Grice, 2015;Roessig et al, 2019). In terms of an autosegmental-metrical analysis, like GToBI (Grice et al, 2005), L+H * , and H * pitch accent types are described by a rising movement and result in positive onglide values.…”
Section: Methodsmentioning
confidence: 99%
“…Tonal onglide is a continuous variable that represents both the direction of the pitch movement as well as the magnitude of this movement, but it does not capture all relevant details of pitch accents (see Grice et al, 2017 for an investigation of the characteristics of pitch accents in terms of tonal onglide and its relation to other parameters). Nevertheless, it has been shown that the tonal onglide movement is a perceptually relevant parameter of pitch accents in German Ritter and Grice, 2015). Two labelers with training in prosody annotated the f0 movements with a simple labeling scheme without having access to the intended focus structures of the sentences: First, the labelers identified all utterances in which the speaker did not place the nuclear pitch accent on the object.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two analyses are reminiscent of the much debated on-ramp and off-ramp analyses of rise-fall pitch patterns in Germanic languages (Baumann et al, 2007;Chen, 2011;Gussenhoven, 2008Gussenhoven, , 2016Hanssen et al, 2008;Ritter & Grice, 2015). Importantly, in Germanic as in Romance languages, the two analyses make different predictions with respect to which part of the contour is the most relevant communicatively and perceptually, and which part of the contour is more carefully and precisely produced in cases of enhancement or in different segmental contexts that may impact on tonal realization.…”
Section: Rise-fall Pitch Pattern and The Narrow Focus Contourmentioning
confidence: 99%
“…While English analyses focus on the f0-movement after the tone that is associated with the stressed syllable (e.g., H*L, L*H), many German analyses focus on the f0-movement leading up to the starred tone (e.g., L+H*, H+L*). Recent perception data from German showed that listeners are sensitive to the manipulation of such onglide movements in rising prenuclear and nuclear accents [12,13]. While no data from English are as yet available to be compared with this finding, it is possible that German listeners redeployed their sensitivity for rising onglides to the discrimination of the current stimulus pairs.…”
Section: Discussionmentioning
confidence: 95%